Analisis Manajemen Risiko Terhadap Implementasi Mobile Banking Pada Bank Syariah - Puji Lestari (Journal of Islamic Entrepreneurship and Business Research, 2025)
The rapid advancement of digital technology has transformed various aspects of life, particularly in the economic sector. The banking industry, including Islamic banks, has adapted to technological progress by introducing innovations to enhance operational efficiency. Information and communication technology play a crucial role in maintaining banking operations, enabling the development of digital banking services such as mobile banking applications and web-based banking platforms. Digitalization has significantly reshaped financial transactions, providing customers with greater convenience while simultaneously exposing them to new risks. The increasing use of mobile banking is accompanied by a rise in potential security threats due to the accessibility of digital financial services. This study aims to analyze the risks associated with mobile banking usage and the strategies employed by Islamic banks to mitigate these risks. Using a qualitative descriptive approach, this study explores the challenges posed by mobile banking, particularly in the context of Islamic banking, and examines the measures implemented to ensure secure and efficient financial transactions. The findings indicate that risks such as data breaches, cyber fraud, and unauthorized access are among the primary concerns in mobile banking. To address these issues, Islamic banks implement various security measures, including encryption, multi-factor authentication, and continuous system monitoring. Furthermore, compliance with Shariah principles is integrated into digital banking security frameworks to ensure ethical financial practices. The study concludes that while mobile banking offers numerous benefits, addressing security risks is essential to maintaining customer trust and safeguarding financial stability in the Islamic banking sector.